A mini review of haloalkane dehalogenase: From molecular characterization to applications - Hasan, Khomaini (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2018)
Haloalkane dehalogenases (HLDs) are hydrolytic enzymes that catalyze a removal of halogenated species in many toxic halogenated compounds. These enzymes belong to hydrolase family that mostly adopt a typically a/b hydrolase structure. They have many potential applications, such as industrial biocatalysis, pharmaceutics, biosensors, or detoxification of chemical weapons. In this review, structure, mechanism and applications of these enzymes will be discussed.